Rainbow factors in hypergraphs - Coulson, M; Keevash, P; Perarnau, G; Yepremyan, L (2018)
For any $r$-graph $H$, we consider the problem of finding a rainbow $H$-factor in an $r$-graph $G$ with large minimum $\ell$-degree and an edge-colouring that is suitably bounded. We show that the asymptotic degree threshold is the same as that for finding an $H$-factor.